Early Eating Patterns and Overweight and Obesity in a Sample of Preschool Children in South-East Poland - Baran, Joanna (Int J Environ Res Public Health, 2019)
The aim of this study was to assess the impact of a child’s diet in the first year of life (breastfeeding duration, introduction of solid meals to the diet, the time of starting nutrition consistent with an adult diet) on the prevalence of overweight and obesity in preschool age. Three-hundred children aged 4–6 were included in the analysis. The children’s height and body weight were assessed and their body mass category was determined based on the BMI (Body Mass Index) percentile. Parents provided a photocopy of the child’s health book (with information concerning breastfeeding period, start of eating the same meals as the rest of the family, etc.). Obese children were breastfed for the shortest time, cow’s milk was introduced to their diets the earliest, they started eating the same food as the rest of the family the earliest, and they received vegetables, fruits, cereals, and meat products in their diet the latest. The results of this study suggest that extending the breastfeeding period beyond 6 months, starting to feed the child the same meals as the rest of the family after 12 months of age, and later introduction of cow’s milk to the diet would reduce the risk of the occurrence of excessive body weight in preschool children.